Gens una sumus?! Or does political ideology affect experts' aesthetic judgment of chess games - Björn Frank; Stefan Krabel (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
This paper presents evidence on biased voting by jurors from the Warsaw Pact countries who ranked high-level chess games. The roots of this bias are probably ideological, as there were no formal benefits for biased voting. Furthermore, this bias is observed only for jurors from Eastern countries, not for those from the West (NATO), and most interestingly, it disappears after the collapse of the Warsaw pact in 1989.
Keywords: 330; Spiel; Abstimmung; Bias; Ideologie; Osteuropa